Plant-wide control design for fuel processor system with PEMFC - Nieto Degliuomini, Lucas (2012)
The main contribution of this work is the application of a novel technique for the plant- wide control design to a challenging bio-ethanol processor system for hydrogen produc- tion. It is based on steam reforming, followed by high and low-temperature shift reactors and preferential oxidation. The obtained hydrogen feeds a fuel cell for automotive use. The control structure is defined by using a well-tested, systematic and generalized procedure, named minimum square deviation. It allows keeping the process at the operating point of maximum efficiency. This design procedure accounts both, set point as well as distur- bances effects which can be sorted according to their importance through specific weighting matrices. The first step of this approach solves the problem of obtaining the best-controlled variables. Then, the search involves testing several combinations between the available inputeoutput variables. The overall processor system with fuel cell, able for doing the tests, was modeled by using mass and energy balances, chemical equilibrium, thermodynamic models and feasible heat transfer conditions. The selected control struc- ture is rigorously tested applied in the dynamic model of the complete plant. The computational implementation of this model was made by using a suitable integration of three well-known programs: MATLAB, HYSYS and ADVISOR. The simulations are per- formed for hybrid vehicle (PEMFC and supercapacitors). The disturbance profile corre- sponds to a urban standard driving cycle, which is one of the most exigent. The conclusions are based on fuel consumptions, typical performance indexes used for control strategy evaluations and a trade-off between cost investments and efficiency.